Francesco Filelfo, Man of Letters. - Jeroen De Keyser (Volume Editor)
1 online resource.
Keywords: Investigating the oeuvre of the Italian humanist Francesco Filelfo (1398-1481), this collection is the first to make extensive use of the critical editions of Filelfo’s numerous writings – in particular of his Epistolarium , published in 2016 by Jeroen De Keyser, who also edited this volume. Uncovering a lot of new information not previously mentioned in the literature on Filelfo, twelve specialized scholars draw attention to long-neglected material, shedding new light on Filelfo’s intellectual endeavors and his literary journey between Greek and Latin. This illuminating collection offers historians of ideas as well as literary scholars and Neo-Latinists new inroads into Filelfo’s vast oeuvre, and through it to the world of Quattrocento humanism. Contributors include: Jean-Louis Charlet, Guy Claessens, Jeroen De Keyser, Tom Deneire, Ide François, James Hankins, Noreen Humble, Gary Ianziti, Han Lamers, David Marsh, John Monfasani, and Jan Papy.